Collaborative Model Strategy Through Co-Innovation and Government Empowerment Programs to Enhance Regional Performance in Poverty Alleviation in West Java - Yakin, Cecep Nurul; Rahayu, Agus; Disman, Disman; Wibowo, Lili Adi (Jurnal Manajemen Pelayanan Publik, 2025)
This study aims to provide an in-depth analysis of the influence of collaborative strategy, co-innovation, and empowering government on regional performance in poverty alleviation in West Java. Addressing empirical, theoretical, and research gaps, the study seeks to bridge existing literature by examining these relationships in a context where prior research is limited. Employing a descriptive and verification design with a quantitative approach, data is collected through questionnaires distributed to the Poverty Alleviation Coordination Teams (TKPKD) across 27 regencies and cities in West Java. The study utilizes non-random quota sampling and processes the data using Partial Least Squares Structural Equation Modeling (PLS-SEM) to ex-plore both direct and mediated effects among the variables. The anticipated results suggest that collaborative strategy positively influences re-gional poverty alleviation performance, both directly and indirectly through the me-diating roles of co-innovation and empowering government. Additionally, the study expects to reveal that geopolitical factors, government policies, and bureaucratic leadership significantly shape the implementation of collaborative strategies in the region. This research makes a novel contribution by addressing a significant empirical gap in the study of collaborative strategies in poverty alleviation within West Java.